Current airframe manufacturing technologies in the aeronautical industry and trends for future developments - Vieira, Paulo António Gouveia (2014)
The aeronautical industry is an area in constant change. The aircraft as a product is evolving, making use, most of the times, of new revolutionary materials and manufacturing processes. At the same time, the global market is expanding quickly and new players are entering the market in increasing competition. At this point, it is, thus important to analyze the options that manufacturers have at their disposal to tackle with this new environment. Having this in mind, this work aimed at assessing the current manufacturing technologies, focused on the biggest part of the aircraft, the airframe, analyzing in particular the application of composite materials and lightweight metal alloys and their implications in production and operations. In this scope, the current state and future trends of materials, environmental sustainability, processes, joining, repairing and inspection methods, are assessed, always from the point of view of the design, taking into account the advantages and disadvantages of composite materials and of the lightweight metal alloys, as well as the obstacles to their development and application. When analyzing the future trends in material’s application, a study is presented to quantify those trends for the most important materials in aircraft construction, from which conclusions were derived covering aspects related with the evolution of the mix of materials, in the years to come, in what aircraft construction is concerned, based on historical data from a substantial collection of aircraft data.